2007
DOI: 10.1055/s-2007-965118
|View full text |Cite
|
Sign up to set email alerts
|

Cold Water Recovery Reduces Anaerobic Performance

Abstract: This study investigated the effects of cold water immersion on recovery from anaerobic cycling. Seventeen (13 male, 4 female) active subjects underwent a crossover, randomised design involving two testing sessions 2 - 6 d apart. Testing involved two 30-s maximal cycling efforts separated by a one-hour recovery period of 10-min cycling warm-down followed by either passive rest or 15-min cold water immersion (13 - 14 degrees C) with passive rest. Peak power, total work and postexercise blood lactate were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 16 publications
(31 reference statements)
4
77
2
6
Order By: Relevance
“…A significant decrease in CMJ, RJA and rRST performance was observed immediately after the CWI. In line with these results, Crowe et al 8 observed a decrease in anaerobic performance (30-s "all out" maximal cycling test) after CWI (15 min at 13-14 o C). In this study, peak power, total work and post-exercise blood lactate were significantly reduced following CWI compared to the first exercise test and the control condition 8 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…A significant decrease in CMJ, RJA and rRST performance was observed immediately after the CWI. In line with these results, Crowe et al 8 observed a decrease in anaerobic performance (30-s "all out" maximal cycling test) after CWI (15 min at 13-14 o C). In this study, peak power, total work and post-exercise blood lactate were significantly reduced following CWI compared to the first exercise test and the control condition 8 .…”
Section: Discussionmentioning
confidence: 59%
“…In line with these results, Crowe et al 8 observed a decrease in anaerobic performance (30-s "all out" maximal cycling test) after CWI (15 min at 13-14 o C). In this study, peak power, total work and post-exercise blood lactate were significantly reduced following CWI compared to the first exercise test and the control condition 8 . Buchheit et al 24 did not show a significant difference in mean power output and completion time during 1-km cycling time trials between the CWI (5 min at 14 o C) and passive recovery in male cyclists, despite the improvement of perceived rating of recovery after the CWI.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous study suggested that CWI caused peripheral vasoconstriction and a decrease in blood flow to the active muscles. hypothetically, reduction in muscle blood flow can be cause an antiinflammatory effect and help to muscle recovery [12]. Furthermore, it is shown that …”
Section: Discussionmentioning
confidence: 98%
“…Schniepp et al and Crowe et al reported that maximum and average power was negatively affected by CWI (compared to the passive rest) when performance tests were one hour apart. The results of these previous studies showed that athletes need to consider the timing of events when deciding whether or not to employ CWI recovery [11,12]. Previous study suggested that CWI caused peripheral vasoconstriction and a decrease in blood flow to the active muscles.…”
Section: Discussionmentioning
confidence: 99%